2015
DOI: 10.18186/jte.55930
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTAL PERFORMANCE OF R134a AND R152a USING MICROCHANNEL CONDENSER

Abstract: An experimental performance study on vapour compression refrigeration system with R134a and drop in substitute R152a with aluminium microchannel condenser was carried out for condensation temperature of 48°C while evaporation temperature varied from -10 to 15°C. Refrigerant charge of R152a was reduced by 40% over R134a with the microchannel condenser. Performance parameters like work input to the compressor, coefficient of performance, refrigerating capacity, condenser capacity and the product of the overall h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…(12). It is noticed that, the percentage increase achieved by Patil et al [1] was 65%, Yun et al [2] achieved percentage increase of 84% while Bhatkar, et al [8] achieved 18%. The figure indicates that percentage increase in pressure drop achieved by the present work is nearly close to that obtained by [8] and less than that obtained by the other two.…”
Section: Fig 11 Effect Of Ambient Temperature On Condenser Pressure mentioning
confidence: 99%
See 2 more Smart Citations
“…(12). It is noticed that, the percentage increase achieved by Patil et al [1] was 65%, Yun et al [2] achieved percentage increase of 84% while Bhatkar, et al [8] achieved 18%. The figure indicates that percentage increase in pressure drop achieved by the present work is nearly close to that obtained by [8] and less than that obtained by the other two.…”
Section: Fig 11 Effect Of Ambient Temperature On Condenser Pressure mentioning
confidence: 99%
“…However, the heat convection coefficient obtained by Kim correlation is less than that of this work by about (2.2:3.4 %). [14] and Shah [15] correlations (8) and 9…”
Section: Fig 14 Comparison Of Convective Transfer Coefficient Calculmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported that refrigerant R290 and its mixtures performs well and can be a better substitute to CFC and HCFC refrigerants in various applications [8][9][10][11][12][13][14][15][16][17][18][19].Purkayasthaet. al.…”
Section: Introductionmentioning
confidence: 99%
“…While, the refrigerant charge amount for the system with the microchannel condenser was 9.2% smaller than that with the round-tube condenser. Bhatkar et al [6] studied in the performance of of R134a and R152a using aluminum microchannel condenser experimentally. The experiments were carried out for condensation temperature of 48°C while evaporation temperature varied from -10 to 15°C.…”
Section: Introductionmentioning
confidence: 99%